Real-time specific absorption rate supervision for a 32-channel RF transmit system with virtual observation points - Fiedler, Thomas M.; Orzada, Stephan; Grimm, Johannes A.; Batkai, Bottyan; Dinkelacker, Stefan; Kratzer, Fabian; Klein, Christoph; May, Markus W.; Mayer, Falk; Schweins, Luisa; Ladd, Mark E. (Magnetic resonance in medicine, 2025)
Purpose Real-time supervision is a crucial element of an RF parallel transmit (pTx) system to supervise safety of the subject during MR imaging and to utilize the full potential of the RF array. However, the computational demand for the specific absorption rate (SAR) calculation scales much greater than linearly with the number of RF channels. Furthermore, a high number of virtual observation points (VOPs) for the local SAR supervision is preferable to reduce the SAR overestimation during the VOP compression, increasing the computational demand further. An RF transmit supervision system for a 32-channel pTx system including local SAR calculation with a high number of VOPs was developed. Methods The system includes 64 digitizer channels to measure the real and imaginary parts of 32 transmit channels. To handle the high computational demand, local SAR calculation is performed on a graphics processing unit (GPU). SAR is averaged for 10 s and 6 min. The system operates independently of the MR system and shuts down the RF power amplifiers (RFPAs) if a SAR limit is exceeded, or the supervision system is interrupted. Results The presented system is able to monitor 32 transmit channels and perform real-time SAR calculation with up to 165 000 VOPs. When using only 16 or 8 channels, the number of VOPs increases to 730 000 and 2 300 000, respectively. Conclusion In this work, we present a real-time RF supervision system designed to monitor a 32-channel pTx systems including the relative phases of each channel and to perform the local SAR calculation based on VOPs from numerical simulations.
Gesehen am 01.12.2025